Antibiotic use in patients with acute cholecystitis after percutaneous cholecystostomy. Issue 2 (February 2020) - Wu, Pei-Shan; Chou, Chung-Kai; Hsieh, Yun-Chen; Chen, Chun-Ku; Lin, Yi-Tsung; Huang, Yi-Hsiang; Hou, Ming-Chih; Lin, Han-Chieh; Lee, Kuei-Chuan
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Currently, evidence regarding the strategies of antibiotic use in patients with acute cholecystitis after receiving percutaneous cholecystostomy is limited. Hence, we aimed to investigate the outcomes in patients with inoperable acute cholecystitis receiving narrow or broad-spectrum antibiotics after percutaneous cholecystostomy. Methods: A total of 117 patients receiving percutaneous cholecystostomy were categorized into moderate and severe acute cholecystitis defined by the Tokyo guideline and then divided into group A (narrow-spectrum antibiotic use) and group B (broad-spectrum antibiotic use). The clinical outcomes and complications were analyzed. Results: In moderate acute cholecystitis (n = 80), group A patients (n = 62) had similar early recurrent rate (11.3% vs 16.7%; p = 0.544) and a shorter length of hospital stay (13.4 ± 8.6 vs 18.6 ± 9.4 days; p = 0.009) as compared with group B patients (n = 18). No in-hospital mortality occurred in moderate acute cholecystitis. In severe acute cholecystitis (n = 37), both groups had similar length of hospital stay (16.3 ± 12.2 vs 20.9 ± 9.5 days; p = 0.051), early recurrent rate (0% vs 16.7%; p = 0.105), and in-hospital mortality rate (5.3% vs 16.7%; p = 0.340). Although group B patients with severe cholecystitis had higher serum levels of alkaline phosphatase (Alk-P) and higher proportion of underlying malignancy, American Society of Anesthesiologists (ASA) class IV and septic shock, the clinical outcomes were not inferior to patients in group A. Conclusion: In moderate acute cholecystitis after percutaneous cholecystostomy, patients receiving narrow-spectrum antibiotics have comparable clinical outcomes as those treated with broad-spectrum antibiotics. However, in severe acute cholecystitis, broad-spectrum antibiotics might still be necessary to rescue these patients.